2018
DOI: 10.1088/1681-7575/aaee37
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt determination in the hair of patients after metal-on-metal hip implants by instrumental neutron activation analysis

Abstract: In these years, following the alert of possible problems of toxicity issued by national medicine authorities, thousands of patients with hip implants are recalled for a set of analysis, including cobalt determinations in blood and urine. In this framework, additional measurements of cobalt in hair are recommended to monitor the release of metals in the body after surgery. Aiming at a clinical application, the standardization of the hair washing protocol used to remove possible external contamination is essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…[ 13 ] and in agreement with the results we previously obtained with the same person, that is, the control subject C2 reported by D’Agostino et al. [ 11 ]. Conversely, the 4.3 mg kg -1 preoperation Co mass fraction mean value reported by Fu-Cun et al.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…[ 13 ] and in agreement with the results we previously obtained with the same person, that is, the control subject C2 reported by D’Agostino et al. [ 11 ]. Conversely, the 4.3 mg kg -1 preoperation Co mass fraction mean value reported by Fu-Cun et al.…”
Section: Resultssupporting
confidence: 92%
“…The quality and metrological traceability of hair analysis carried out in this study are supported by the use of the IAEA washing method, demonstrated to be suitable to remove the unbound Co component [ 11 ], and the agreement between the LTCS and INRIM intercomparison results plotted in Figure 2 . In addition, particular attention was paid to the exclusion of hair samples with insufficient mass and results below the measurement detection limit.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations